EVALUASI IMPLEMENTASI ANGGARAN BERBASIS KINERJA PERFORMANCE-BASED BUDGETING TERHADAP AKUNTABILITAS ANGGARAN PENDAPATAN BELANJA NEGARA - Muhammad Yazid Khofi; Inka Nusamuda Pratama; Ikram; Firra Nurfajriah; ZhelinTri Sah Billah; Suci Ramadani; Sigit Karma Syaputra; Akmal Muliadi; Buhari; Muliawan (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to determine the implementation of performance-based budgeting on the APBN. The writing of this article uses the literature review method, which is a search or review of published research articles. The process of searching for research data sources used in this article is searched through the Internet using a search engine. The data sources that we searched on the internet related to the evaluation of the implementation of performance-based budgeting on APBN accountability. The process of making this article began with reviewing data sources, these data sources were in the form of academic journals, media reviews, documents, both national and international documents related to the research title. The results of the study showed that the use of APBN budgeting with a performance-based budgeting system was better than using the Line Item budgeting system. The performance-based budgeting system for APBN has not been fully implemented properly.